If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y = 11 + -1x Solving -2y = 11 + -1x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-2'. y = -5.5 + 0.5x Simplifying y = -5.5 + 0.5x
| (r+9)(r+3)=0 | | 0.5m^2+2m+2=0 | | 0.6-4.4-4.8=2.4 | | 3t^2+2t-7=0 | | 3t^2-5t+1=0 | | 9x^2=x+5 | | 8a+4am=144 | | 0.6x^2=2.4x+.6 | | B=0.7 | | r^2+4r+5=0 | | x^2-6x+5=-8 | | 83x+11= | | 22p=110 | | 72=8n | | 14v=3 | | 14=3c | | -5r=-4 | | -5=-4r | | 2x=x^2-5 | | 15=7n | | 12=2w | | 10x-4= | | 3(a+4)=4(a-1) | | 12w=2 | | -2x+9x+5=-2 | | 15c=90 | | -5x=-22 | | 9x^2=45x | | 10x-4+10x+7= | | 4(x+3)=6x+6-2x | | 18+12e=-20 | | 2w+2(3w-7)=146 |